111 THE INFLUENCE OF THE ANDAGO® ON GAIT PARAMETERS AMONG OLDER ADULTS IN THE POST-ACUTE REHABILITATION SETTING: A PILOT STUDY. (25th October 2022) - Fay, A; Synott, E; McDaid, E; Barrett, E
Abstract: Background: Electromechanical devices incorporating body-weight support have been developed to enable a repetitive approach to gait rehabilitation whilst decreasing physical strain on treating therapists. The Andago® gait trainer provides dynamic body weight support for individuals while simultaneously enabling them to walk overground. The purpose of this study was to compare the effect of the Andago® versus conventional overground walking on gait parameters, fear of falling (FOF) and ratings of perceived exertion in a post-acute rehabilitation population. Methods: Patients undergoing rehabilitation were randomly assigned to the Andago® or conventional walking condition on day one with the alternate testing condition completed on day two. Participants completed a 10-metre walk test where stride length, walking speed and cadence were recorded. Participants then undertook a 20-minute gait re-education session where number of steps, distance walked and number of siting breaks were recorded. Ratings of perceived exertion (BORG) and FOF scores were recorded at minutes 1, 10 and 20. Results: Twenty-seven participants (mean age 78 (SD 9.2), female 55.6%(n=15)) completed the study. Reasons for rehabilitation included neurological (51.8%; n= 14), orthopaedic (33.3%; n=9) and medical conditions (14.8%; n=4). Forty-four percent of participants (n=12) had a mild cognitive impairment. Body weight support ranged from 10% to 17% (mean 11%, SD 2). No significant differences in the 10-metre walk test were found between conditions. A reduction in the number of sitting breaks (p <0.05) and FOF at minutes 10 (p<0.05) and 20 (p<0.05) was found in favour of the Andago® during the gait re-education session. Conclusion: Preliminary results suggest the Andago® is a feasible modality for gait re-education in patients undergoing rehabilitation, being at least comparable to conventional overground gait training. A reduction in FOF in patients coupled with decreased physical strain on therapists may provide opportunities for more intensive practice and warrants further investigation.